Janet Wolff: 'The Aesthetics of Uncertainty' - Jakub Stejskal (Estetika, 2009)
A review of Janet Wolff’s The Aesthetics of Uncertainty (New York: Columbia University Press, 2008, ix + 183 pp. ISBN 978-0-231-14096-6)